The association of bone attrition with knee pain and other MRI features of osteoarthritis. Issue 1 (14th May 2007) - Hernández-Molina, G; Neogi, T; Hunter, D J; Niu, J; Guermazi, A; Reichenbach, S; Roemer, F W; McLennan, C E; Felson, D T
Abstract : Objective: To determine whether bone attrition (flattening or depression of the subchondral bone) was associated with the presence and severity of knee pain and to evaluate the coexistence of attrition and other MRI features likely associated with pain. Methods: Participants in the Framingham Osteoarthritis Study, a community cohort unselected for OA, answered questions about knee pain and underwent knee x rays and MRI. Attrition, bone marrow lesions (BMLs) and effusions were scored on MRI using the WORMS scale. We assessed attrition in knees with and without pain, and using logistic regression examined its association with pain adjusting for age, gender, Kellgren–Lawrence (K–L) grade, BMI, BML and effusion. We also explored the relation between attrition, pain severity and nocturnal pain. Results: Attrition (Grade ⩾2) was present in 28% (167/592) of painful knees and in 10% (106/1035) of non-painful knees (adjusted OR 1.6 (95% CI 1.1 to 2.2)). Of knees with OA (n = 368), 74% had pain if attrition was present and 58% if it was absent (adjusted OR 1.2 (95% CI 0.7 to 2.0)). Of knees without OA (n = 1222), pain was reported in 39% of knees with attrition and in 27% without it (adjusted OR 2.1 (95% CI 1.1 to 4.0)). We found no association between either attrition/pain severity or attrition/nocturnal pain. Attrition often co-occurred with other OA features associated with pain such as BMLs and effusions. Conclusions: Attrition was associated independently with knee pain. Unlike knees without OA, the association was lost in OA knees where other pathological features that may cause pain also coexisted.